2006
DOI: 10.1590/s0124-00642006000400003
|View full text |Cite
|
Sign up to set email alerts
|

Lepra Conyugal

Abstract: Conjugal leprosy Objectives Determining the occurrence of leprosy amongst couples and establishing the type of leprosy in index and secondary cases. Methods The characteristics of leprosy were studied between 1980 and 2000 in Atlántico Department located on the Colombian Caribbean Coast. Clinical histories of patients registered in the Leprosy Control Programme were reviewed. Clinical exams were performed and personal interviews carried out with couples suffering from leprosy. Results Twenty-six married couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…A Brazilian study in 1957 found conjugal transmission in 7.8%, occurring in 50 of 638 cases (Quagliato 1957). Meléndez et al (2006) described a conjugal rate of 5.4% in Columbian patients, with consanguinity in two of 26 couples studied; furthermore the pairs were married five-40 years before the second spouse developed clinical symptoms. Chaussinand et al (1960), in France, reported a single case in which the spouse had five years of marital exposure before clinical symptoms developed.…”
Section: Resultsmentioning
confidence: 95%
“…A Brazilian study in 1957 found conjugal transmission in 7.8%, occurring in 50 of 638 cases (Quagliato 1957). Meléndez et al (2006) described a conjugal rate of 5.4% in Columbian patients, with consanguinity in two of 26 couples studied; furthermore the pairs were married five-40 years before the second spouse developed clinical symptoms. Chaussinand et al (1960), in France, reported a single case in which the spouse had five years of marital exposure before clinical symptoms developed.…”
Section: Resultsmentioning
confidence: 95%
“…9 Para infectarse con el bacilo de Hansen y desarrollar la enfermedad, hay entonces mayores posibilidades cuando existe un contacto íntimo y repetido, muy evidente en los casos de EH infantil, especialmente, el contacto madrehijo y el contagio entre parejas. 10,11 La predisposición innata a la infección parece ser particularmente crucial para la EH: se estima que solo una pequeña fracción (del 5 al 12%) de las personas expuestas a M. leprae se infecta con éxito. 12 Durante el periodo 2012-2017, se registraron en Costa Rica 51 casos nuevos de EH con prevalencia a nivel nacional de 0,06 casos por diez mil habitantes.…”
Section: Fecha Recibido: 25 De Febrero 2020unclassified